Resposta pulpar após uso de materiais capeadores em pulpotomias: análises histológicas - Santos, Laís Da Silveira Terra (2016)
This research aimed to evaluate histologically the inflammatory response at 15 and 30 days of Wistar rats mandibular first molars pulp after pulpotomy using white Mineral Trioxide Aggregate (MTA) and 15,5% Ferric Sulphate (FS) as capping materials. Sixteen male Wistar rats were randomly divided into two experimental groups (MTA and FS) and then divided into two subgroups according to the experimental period (15 and 30 days). After the euthanasia of the animals, the teeth were extracted in block with surrounding bone, prepared and stained with Hematoxylin and Eosin (HE) for histological analysis. Only one tooth of the SF 15 days group showed apical periodontitis, all other teeth kept their vitality with some degree of inflammation in the remaining pulp. The inflammatory infiltrates was higher in the 15 days period, there was a regression in the 30 days period at both tested materials and the histological normality of the remaining pulp were better on the teeth treated with MTA than on those treated with FS, wich showed a replacement of part of the pulp tissue for blood clot and remaining of necrotic tissue. However, no statistically difference was found between the groups.